REKONSTRUKSI PENDIDIKAN PERPAJAKAN: SUATU KAJIAN KRITIS TENTANG ETIKA PROFESI DALAM PERSPEKTIF KRITIS KI HADJAR DEWANTARA - Widyaningrum, Tri Rahayu; Triyuwono, Iwan; Djamhuri, Ali (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
Quality education is needed for the improvement of human resources. The contribution given by the education world will color society's behavior. For that education should be able to give birth to the learner in accordance with the needs of the era and have the ideal values ​​of science. Taxation education should not only be technical to give birth to a person capable of calculating taxes according to Law, but also need to have ethical based tax personality aspects. Ethics have an enormous influence and their absence will have a negative impact on the educational outcome own. Tax issues at various levels of interest have shackled the practice of taxation in the country, it appears not apart from the moral problems that ditenggarai be a source of trouble. Therefore, it is necessary to have ethical content in tax education as a moral principle and guidance of learning. There are 5 informants in this research, all involved in the field of taxation education such as students, teachers, head of taxation department and tax consultant. This research uses the critical paradigm of Ki Hadjar Dewantara as the Father of National Education. The results of this study indicate that the material taxation provided does not have ethical elements. Teaching is only technical skill without taking into account the importance of ethics. In the perspective of Ki Hadjar Dewantara, this model of education is not in accordance with the essence of science itself, where in the educational process it is necessary to plant Budi Pekerti attached to ethics in relation to taxation education as implied in the thought of Ki Hadjar Dewantara